2013
DOI: 10.1001/jama.2013.1948
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Presenting Complaint vs Discharge Diagnosis for Identifying “ Nonemergency” Emergency Department Visits

Abstract: ITH INCREASING MEDIcal care costs, policymakers have turned to emergency department (ED) utilization as a potential source for cost savings. Although the assumptions driving this policy approach are unproven, 1 recent attempts to reduce ED use have occurred in Medicaid programs. [2][3][4][5][6] If implemented for patients in Medicaid programs, it is likely that such practices may result in similar policies by other payers, potentially affecting access to ED care for other segments of the population.One approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
165
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 22 publications
5
165
0
3
Order By: Relevance
“…11 Another study examined reasons for patient presentation to the ED in Edmonton, Alberta. 12 The study found that many patients made concerted efforts to avoid ED visits; 61% of patients sought alternative care before visiting the ED. 12 The role of health professionals and systems in driving ED overuse must be considered.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…11 Another study examined reasons for patient presentation to the ED in Edmonton, Alberta. 12 The study found that many patients made concerted efforts to avoid ED visits; 61% of patients sought alternative care before visiting the ED. 12 The role of health professionals and systems in driving ED overuse must be considered.…”
Section: Resultsmentioning
confidence: 98%
“…12 The study found that many patients made concerted efforts to avoid ED visits; 61% of patients sought alternative care before visiting the ED. 12 The role of health professionals and systems in driving ED overuse must be considered. Strikingly, 47% of patients who sought alternatives to the ED made contact with a physician's office.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations